Prevalence of Scabies and Its Diagnostic Methods in Dermatological Centers of Kabul City - Rasekh, Hamidullah; Mozaffari, Rahmatullah (Journal of Natural Sciences – Kabul University)
Scabies is a skin disease caused by the parasite Sarcoptes scabiei, which leads to severe itching. Approximately 200 million people worldwide are affected by scabies. This study aims to assess the prevalence of scabies and evaluate its diagnostic methods in healthcare centers in Kabul. The study used a questionnaire to collect and analyze demographic information and risk factors associated with the disease. The results indicate that scabies accounts for 15.94% of skin diseases. The infection rate was higher in males (59.1%) compared to females (40.9%), and it was more prevalent among single individuals (53.7%) than married individuals (46.3%). Among those affected, the prevalence was notably high in individuals aged 19–39 years (30.8%), those with primary education (29.3%), those with poor economic status (43%), individuals from larger families (75.8%), and those who had a history of contact with an infected person (69.7%). All in all, the high prevalence of scabies among skin conditions presents a significant challenge. Despite the availability of effective diagnostic methods, scabies in these centers is primarily diagnosed based on clinical symptoms. Implementing appropriate diagnostic techniques is essential for effective disease management.